Confronting mistakes lessons from the aviation industry when dealing with error - Hagen, Jan U. (Palgrave Macmillan, 2013)
"In most organizations, errors, although common and unavoidable, are rarely thoroughly examined. Peers may be reluctant to talk about the mistakes one of them has made, whereas superiors prefer to discuss the mistakes of their subordinates with them in private. Based on interviews with over 360 managers from a range of sectors about how they deal with error, the authors of this innovative and unique book present a framework of "open error management" and demonstrate its benefits via dramatic case studies from the aviation industry. Including compelling case studies from international aviation companies, the result is an innovative and unique approach to analyzing business strategy"-- c Provided by publisher